filmov
tv
If y=e^tan^-1(x),prove that (1+x^2)Yn+2+(2(n+1)x-1)Yn+1 + n(n+1)Yn=0{based on Leibnitz Theorem}
![preview_player](https://i.ytimg.com/vi/rtDu5QW0geY/maxresdefault.jpg)
Показать описание
In this video we are going to solve an interesting question which come in Du university exam
we are going to look into it
How we can soove it? which theorem should we use and how
these are all we do
we are going to look into it
How we can soove it? which theorem should we use and how
these are all we do
If y=e^tan^-1(x),prove that (1+x^2)Yn+2+(2(n+1)x-1)Yn+1 + n(n+1)Yn=0{based on Leibnitz Theorem}
If y= e^tan-1 x prove that (1+x^2)yn+2 +[(n+1)x-1]yn+1 +n(n+1) yn =0 | Successive differentiation
Leibnitz Theorem question solve.|| y=tan^-¹x then prove (1 + x²)yn+2 + 2(n + 2)xyn + 1 + n (n + 1)yn...
If `y=e^tan^((-1)x)` , prove that `(1+x^2)y_2+(2x-1)y_1=0` .
y= tan^-1 P.T(1+x^2)yn+1+2nxyn+n(n-1)yn-1=0 by Leibnitz theorem
If y = e^sin-1 x, prove that (1-x^2)yn+2 - (2n+1)yn+1 - (m^2+n^2)yn=0. Hence find yn for x=0 || #24
If y= e^asin^-1x , prove that (1-x²)yn+2-(2n+1)xyn+1-(n²+a²)yn= 0. Hence find yn at x= 0
If y = (sinh^-1 x)^2, prove that (1+x^2) yn+2 + (2n+1)xyn+1 + n^2yn =0|Leibnitz Theorem problems|#23
x=tan(logy) , Prove that (1+x^2)yn+1 +(2nx-1)yn+n(n-1)yn-1=0 | Leibniz Rule | Bsc Math #maths
If y=e^tan^(-1)x prove that (1+x^2) (d^2 y)/(dx^2)+(2x-1) dy/dx=0
If y= cos(msin^-1x), show that (1-x²)yn+2 -(2n+1)x yn+1 -(n²-m²)yn= 0
y=tan^-1 x prove that (1+x^)y2+2xy1=0 derivative
If y=(x^2-1)^n, show that (x^2-1)yn+1+2xyn+1-n(n+1)yn=0.Hence if P(x=1/2^n.n!d^n/dx^n{(x^2-1)^n}),sh
Nth Derivative Solved Examples In Hindi if y = tan inverse x prove that yn = 1^n! (n-1)!Mathematics
If y= (x+√1+x^2)^m, Prove that (1+x^2)yn+2 +(2n+1)xyn+1 + n^2yn=0|| Leibnitz Theorem problems| #22
If y^1/m + y^-1/m = 2x, prove that (x^2-1)yn+2 +(2n+1)yn+1 +(n^2-m^2)yn =0| Leibnitz Theorem| #26
If y= (x²-1)ⁿ, then prove that (x²-1)yn+2 +2xyn+1 -n(n+1)yn= 0 | Leibnitz Theorem
Leibnitz Theorem question solve. logy=tan^-1 then show that (1+x^2)y2+(2n-1)y1=0 and find nth D
If y = e^acos^-1x prove that (1-x^2)yn+2 -(2n+1)xyn+1 -(n^2+a^2)yn=0 Hencefindthe value of yn forx=0
If `y = tan^-1x, then (1 + x^2) у_2 + 2xy_1 =`
𝐈𝐟 𝐥𝐨𝐠𝐲 = tan-1x I show (1+x2)y2 + (2x-1)y1=0 I higher order derivatives I Class 12...
if y=tan-1x, Prove (1+x^2)y2 + 2xy1 = 0 I class 12 XII I cbse I icse I Higher Order Derivatives
If y=(x^2-1)^n ,prove that (x^2-1)yn+2 +2xyn+1 - n(n+1)yn =0 Hence if Pn = d^n/dx^n {(1-x^2)dPn/dx..
If y = tan⁻¹√(1 + x²) - 1/x , Find dy/dx
Комментарии